2018
DOI: 10.1016/j.ympev.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Vectors of diversity: Genome wide diversity across the geographic range of the Chagas disease vector Triatoma dimidiata sensu lato (Hemiptera: Reduviidae)

Abstract: To date, the phylogeny of Triatoma dimidiata sensu lato (s. l.) (Hemiptera: Reduviidae: Triatominae), the epidemiologically most important Chagas disease vector in Central America and a secondary vector in Mexico and northern South America, has only been investigated by one multi-copy nuclear gene (Internal Transcribed Spacer - 2) and a few mitochondrial genes. We examined 450 specimens sampled across most of its native range from Mexico to Ecuador using reduced representation next-generation sequencing encomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 39 publications
(61 reference statements)
4
39
0
Order By: Relevance
“…aff. dimidiata – cave; Justi et al 2018 ) were compared with all known morphotypes of T. dimidiata s.l. ( T. dimidiata maculipennis : one specimen from Mexico; T. dimidiata capitata : four specimens including the holotype; Triatoma dimidiata s.l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aff. dimidiata – cave; Justi et al 2018 ) were compared with all known morphotypes of T. dimidiata s.l. ( T. dimidiata maculipennis : one specimen from Mexico; T. dimidiata capitata : four specimens including the holotype; Triatoma dimidiata s.l.…”
Section: Methodsmentioning
confidence: 99%
“…Following the synonymizing of the species ( Lent and Wygodzinsky 1979 ), many qualitative and quantitative phenotypic, biochemical, and molecular studies have sought to clarify the systematics of T. dimidiata . Phylogenetic studies of T. dimidiata based on DNA sequence analyses of nuclear and mitochondrial genes ( Bargues et al 2008 , Monteiro et al 2003 , Dorn et al 2016 ) and genome-wide data ( Justi et al 2018 ) have shown that T. dimidiata is composed of at least three phylogenetic species ( Mishler and Brandon 1987 ), referred to as : T. dimidiata sensu strictu (or groups 1 and 2), T. sp. affinnis dimidiata (group 3) and T. sp.…”
Section: Introductionmentioning
confidence: 99%
“…The cryptic dimidiata species complex has been largely supported using molecular tools, which has led to the identi cation of three phylogenetically well-differentiated haplogroups in Mexico and part of Central America [9,11,12], and two taxa have been formally described as new species [37,38]. For the rst time, we used the spot pattern presented by this complex to discriminate among haplogroups (possible cryptic species) by extracting and analyzing quanti able variables from digital images.…”
Section: Discussionmentioning
confidence: 99%
“…However, taxonomic changes have occurred since then, such as descriptions of new species and redescriptions and/or revalidations of others (de Oliveira and Alevi 2017). Thus, there are currently 154 species, including151 extant and three fossil species ( T. dominicana , P. hispaniolae, and Paleotriatoma metaxytaxa ) distributed in 19 genera and grouped into five tribes, taking into account that the Linschosteini tribe has been currently included in Triatomini (Justi et al 2018, Lima‐Cordón et al 2019, Nascimento et al 2019, Poinar 2019). As the evolutionary processes of the triatomines seem to be disruptive (Dujardin et al 2009) and some groups present morphological similarity for the specific diagnosis of the taxa, techniques with a high degree of resolution are necessary to evaluate the specific status and the phylogenetic/morphological relationships (Barretto and Albuquerque 1969, Schofield 1988, Carcavallo et al 2001, Jurberg 2003, de la Fuente et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the emergence of new taxonomic methodologies, several complexes were reorganized based on the need of groupings in natural assemblages (Alevi et al 2012a, 2017, Gardim et al 2014, Pita et al 2016). Currently, triatomines are clustered into six groups, eight complexes, and nine subcomplexes (Alevi et al 2017, Justi et al 2018).…”
Section: Introductionmentioning
confidence: 99%